Digital and Green Transition in the EU27 from an Econometric Perspective - GEORGE-CORNEL DUMITRESCU (Global Economic Observer)
The pandemic and, currently, the war in Ukraine revealed the fragility of the linear economic system that depends on external supply chains and emphasised the need to achieve strategic autonomy regarding the critical resources for the economy and people. Since energy has become a burning issue nowadays, based on data provided by Eurostat and the European Commission, the paper analyses the relationship between the real GDP per capita, the electricity production capacities for renewables and wastes (wind, solar and solid biofuels), and the Digital Economy and Society Index. It aims to identify possible connections between prosperity, digitalisation, and green energy sources in an attempt to understand how to achieve strategic autonomy. The research identified several statistically significant relationships between the GDP per capita, DESI and the components of electricity production capacities for renewables and wastes.